answersLogoWhite

0


Best Answer

As written, that's 4x squared = -21 and x equals the square root of -21/4.

But if you meant that to be 12x, it factors out nicely to (2x + 3)(2x + 3) and x would equal -3/2

User Avatar

Wiki User

โˆ™ 2012-03-09 04:00:54
This answer is:
๐Ÿ™
0
๐Ÿคจ
0
๐Ÿ˜ฎ
0
User Avatar
Study guides

๐Ÿ““
Create a Study Guide

Add your answer:

Earn +20 pts
Q: What the answer to 4x2 plus 12 plus 9 equals 0?
Write your answer...
Submit
Related questions

9x4 plus 27x3 - 4x2 - 12x equals 0?

There are four solutions to 9x4 plus 27x3 - 4x2 - 12x equals 0. One of the solutions is x = -3.


Can you put the equation x2 - 5 -4x2 plus 3x equals 0 in the form ax2 plus bx plus c equals 0?

x2-5-4x2+3x = 0 -3x2+3x-5 = 0 or as 3x2-3x+5 = 0


4x2 plus 2x equals?

Assuming that 4x2+2x = 0: 2x (2x+1) = 0 2x = 0 or 2x+1 = 0 x = 0 or -1/2


4x2 - 2x - 5 equals 0?

4x2 - 2x = 0


How do you solve 4x2 plus 50x equals 0?

4x2+50x = 0 4x(x+12.5) = 0 x = 0 or x = -12.5


How do you factor 4x2 plus 12x plus 9 equals 0?

(2x + 3)(2x + 3)


How do you factor -4x2 plus 3x plus 1 equals 0?

-((4x + 1)(x - 1))


-4x2 plus y2-8x-12y plus 36 equals 0?

dont know sorry


4x2 - 8x plus 3 equals 0?

1/2 , 3/2


How do you solve 4x2 plus 12x equals 0?

4x2 = -12x, divide both sides by 4x: x = -3


4x2-9x plus 1 equals 0?

sure it does... that would be true


How many real solutions are there to the equation shown below 4x2 plus x - 1 equals 0?

2.


How do you solve 4x2 - 4x plus 2 equals 0?

If you can't factor it easily, use the quadratic formula.


Solve x for 4x2-13x plus 3 equals 0?

4x2 - 13 x + 3 = 0 (4x - 1)(x - 3) = 0 x = 3, 1/4


What r the zeros of the function 4x2-5x plus 1 equals 0?

4x2-5x+1 = 0 (4x-1)(x-1) = 0 x = 1/4 or x = 1


What is 12n plus 12 equals 12?

N=0.


What is 4x2 plus 0?

8 (eight)


What is x3 plus 4x2-3x-12 divided by x2-3?

(x3 + 4x2 - 3x - 12)/(x2 - 3) = x + 4(multiply x2 - 3 by x, and subtract the product from the dividend)1. x(x2 - 3) = x3 - 3x = x3 + 0x2 - 3x2. (x3 + 4x2 - 3x - 12) - (x3 + 0x2 - 3x) = x3 + 4x2 - 3x - 12 - x3 + 3x = 4x2 - 12(multiply x2 - 3 by 4, and subtract the product from 4x2 - 12)1. 4x(x - 3) = 4x2 - 12 = 4x2 - 122. (4x2 - 12) - (4x2 - 12) = 4x2 - 12 - 4x2 + 12 = 0(remainder)


If 6 plus 6 equals 12 then what is plus 6 equals 12-6 is this a trick question?

This could be intended as a trick question; the answer is 0. 0 + 6 = 12 - 6


How can you answer this problem 4x2 -2x equals 0?

4x2-2x = 0 2x(2x-1) = 0 x = 0 or x =1/2


What is the discriminant of 4x2-2x plus 4 equals 0?

Discriminant = b2-4ac = (-2)2-(4*4*4) = -60


How do you solve -4x2 plus 5x plus 6 equals 0 by factoring?

-4x2 + 5x + 6 = 0 Multiply through by -1: 4x2 - 5x - 6 = 0 (I prefer the leading coefficient to be >0) 4x2 - 8x + 3x - 6 = 0 4x(x - 2) + 3(x - 2) = 0 (x - 2)(4x + 3) = 0 So x - 2 = 0 or 4x + 3 = 0 ie x = 2 or x = -3/4


Find the value to make each number sentence true 12 plus equals 12?

12 plus 0 is 12


What values best approximate the solutions of -4x2 plus 7x plus 5 equals 0?

Using the quadratic equation formula:- x = -0.5447270865 or x = 2.294727086


-4x2 plus 6x plus 40 equals 0?

-4x2 + 6x + 40 = 0 ∴ -2x2 + 3x + 20 = 0 ∴ -2x2 - 8x + 5x + 20 = 0 ∴ -2x(x + 4) + 5(x + 4) = 0 ∴ (5 - 2x)(x + 4) = 0 ∴ x ∈ {5/2, -4}